Design And Build an Android-Based Educational Gaming App Using Construct 3 Software at PT. EDUCA SISFOMEDIA INDONESIA - Muhammad Djulfikri; Nuraini Purwandari (CSRC Publishing, Center for Sustainability Research and Consultancy Pakistan, 2022)
When it has entered the era of technology that is increasingly developing, one of which is the rampant development of gadgets, especially android-based, which is more owned by users and there are various applications, one of which is games that make children's concentration distracted so that children are more fun to spend their time on gadgets because the display and multimedia offered are not only that games can be played from an early age to an age causing inhibiting reading attention  impact on the shrinking development of education at an early age [1]. To be able to keep pace with the growth that is certainly about to increase until the combination of technology with education that creates educational games can be an important role in the context of learning as a form of innovation. The purpose of this research is to improve a guidance game by using an efficient and instant construct 3 application This research uses the necessary research methodology. The subject of this study is PT. Educa Sisfomedia Indonesia as a game development partner who can help how to improve educational games. The educational aspect of this game has an educational module such as material introduction so that it can again increase interest in reading.